Stabilization of HIF-1α in Human Retinal Endothelial Cells Modulates Expression of miRNAs and Proangiogenic Growth Factors - Lazzara, Francesca; Trotta, Maria Consiglia; Platania, Chiara Bianca Maria; D’Amico, Michele; Petrillo, Francesco; Galdiero, Marilena; Gesualdo, Carlo; Rossi, Settimio; Drago, Filippo; Bucolo, Claudio (Frontiers in Pharmacology, 2020)
Retinal hypoxia is one of the causative factors of diabetic retinopathy and is also one of the triggers of VEGF release. We hypothesized that specific dysregulated miRNAs in diabetic retinopathy could be linked to hypoxia-induced damage in human retinal endothelial cells (HRECs). We investigated in HRECs the effects of chemical (CoCl2) hypoxia on the expression of HIF-1α, VEGF, PlGF, and of a focused set of miRNAs. We found that miR-20a-5p, miR-20b-5p, miR-27a-3p, miR-27b-3p, miR-206-3p, miR-381-3p correlated also with expression of TGFβ signaling pathway genes in HRECs, challenged with chemical hypoxic stimuli. In conclusion, our data suggest that retinal angiogenesis would be promoted, at least under HIF-1α activation, by upregulation of PlGF and other factors such as miRNAs, VEGFA, and TGFβ1.